Pengaruh Penggunaan Model Problem Based Learning terhadap Peningkatan Hasil Belajar IPAS Siswa Kelas IV SD Inpres 6/75 Wellulang - Sudarto Sudarto; Rosmala Rosmala; Alfira Wahyuni (Celebes Science Education, 2026)
This research is a pre-experimental research.that aims to determine whether the use of the problem-based learning model has an effect or not on the science learning outcomes of fourth-grade students at SD Inpres 6/75 Wellulang. The research design used is a one-group Pretest-Posttest design. The population in this study were all fourth-grade students of SD Inpres 6/75 Wellulang with a sample of 12 students selected using saturated sampling techniques. The data collection technique used was a multiple-choice test to determine students' science learning outcomes before and after the use of the problem-based learning model. The data analysis technique used was descriptive and inferential statistical analysis techniques. Based on the results of descriptive statistical analysis, it was found that the pretest value of students' science learning outcomes was in the Sufficient category and the posttest value of students' science learning outcomes was in the Very High category. Based on the results of inferential statistical analysis using paired samples test, it showed that the t-value of 8.749> t-table of 1.79588, which means there was a significant difference in the science learning outcomes of fourth-grade students of SD Inpres 6/75 Wellulang before and after the use of the Problem Based Learning model. Because the science learning outcomes of fourth-grade students of SD Inpres 6/75 Wellulang after the use of the Problem Based Learning model were higher than before the use of the Problem Based Learning model and there was a significant difference, it can be said that the use of the Problem Based Learning model had an effect on improving the science learning outcomes of fourth-grade students of SD Inpres 6/75 Wellulang.